Implementasi IoT Untuk Monitoring Pertumbuhan Tanaman Cabai Dengan Sistem Penyiraman Otomatis Di Desa Kembaran Wetan - Abednego Dwi Septiadi; Yudha Islami Sulistya; Maie Istighosah; Maryona Septiara; Diovianto Putra Rakhmadani; Agatha Dinarah Sri Rumestri (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Kembaran Wetan Village is one of the agricultural areas with chili plants as its main commodity. The main problem faced by farmers is the suboptimal irrigation system, which is still done manually and not based on the actual condition of the land. This community service activity aims to design and implement an Internet of Things (IoT) system to monitor chili plant growth and regulate irrigation automatically. The system consists of five soil moisture sensors, one air temperature and humidity sensor, one rain sensor, and a main controller using an ESP32 connected to a web-based platform. The system is equipped with a dashboard displaying real-time data on soil moisture, temperature, and device status, and can be accessed via a smartphone. The activity also involved training for farmers and ongoing support during the implementation phase. The results of the activity demonstrated that the system can accurately measure soil conditions and regulate irrigation according to plant needs. Farmers also showed interest and readiness to operate the equipment independently. This success indicates that the application of appropriate technologies like IoT has significant potential to enhance efficiency and productivity in rural agriculture in a sustainable manner.